Earth-abundant nanostructured catalysts for solar fuel production at room temperature - Khalifa Said, Ahmed (AUC Knowledge Fountain, 2018)
Improving the performance of solar energy harvesting martials is a challenge facing the renewable energy industry. Over the past few decades, metal oxides have been extensively explored as photoelectrodes for solar-driven production of fuel due to their exceptional stability, semiconducting properties, abundance, and low cost. However, most metal oxides have absorption activity that is limited to the ultraviolet spectral region because of their wide band gap (> 3.0 eV). This is inconvenient because the ultraviolet spectral region contains only 3-5% of all incident solar energy. The current semiconductor technologies resort to either (i) doping as a means of narrowing the band-gap and enhancing light absorption, or (ii) decoration with metals to enhance charge separation. In the first part of the thesis, the synthesis of highly ordered titanium oxynitride nanotube arrays sensitized with Ag nanoparticles (Ag/TiON) was studied for the first time. Ag/TiON proved to be an attractive class of materials for visible-light-driven water splitting. The nanostructure topology of TiO2, TiON and Ag/TiON was investigated using FESEM and TEM. The X-ray photoelectron spectroscopy (XPS) and the energy dispersive X-ray spectroscopy (EDS) analyses confirm the formation of the oxynitride structure. Upon their use to split water photoelectrochemically under AM 1.5 G illumination (100 mW/cm2, 0.1 M KOH), the titanium oxynitride nanotube array films showed significant increase in the photocurrent (6 mA/cm2) compared to the TiO2 nanotubes counterpart (0.15 mA/cm2). Moreover, decorating the TiON nanotubes with Ag nanoparticles (13 Â±2 nm in size) resulted in exceptionally high photocurrent reaching 14 mA/cm2 at 1.2 VNHE. This enhancement in the photocurrent is related to the synergistic effects of Ag decoration, nitrogen doping, and the unique structural properties of the fabricated nanotube arrays. In the second part of the thesis, the effect of Ni alloying with Cu on the electrochemical reduction of CO2 was studied. The GAXRD analysis confirmed the formation of mixed Cu-Ni catalysts. Linear sweep scans showed the Cu70Ni30 to have the lowest overpotential (-0.5VNHE) and highest cathodic current (-1.8mA/cm2). Chronoamperometry measurements, at -0.5 VNHE in CO2-saturated 0.1M KOH, confirmed similar pattern when no limiting current was observed for the electrochemical reduction of CO2. This volcano effect of exceptionally high current and low overpotential was unique for 30% Ni and was attributed to CO2 adsorption and superior charge transfer kinetics.